Career Decision Self-Efficacy Scale-Short Form with Indonesian University Graduates: A Rasch Model Approach - Wening Cahyawulan; Devie Yundianto (ILIN Institute Makassar, 2022)
The Career Decision Self-Efficacy Scale (CDSE)-Short Form is a 25-item intended to assess people's belief in their capacities to make a career decision. This study analyzed the psychometric properties of CDSE-SF using RASCH in the sample of 391 (64% male; 88% female) university graduates in Indonesia. The results indicated that the CDSE-SF are (1) unidimensional except for item number 13 and 17; (2) item measure test showed the greatest value is item number 13 and the lowest value is item number 1; (3) each response of category is functioning well, (4) the item reliability is 0,98 and the person reliability is 0,95, and (6) item number 1, 16, 18, and 22 are detected to have DIF across gender. Overall, the results indicated that based on the psychometric properties of the CDSE-SF Indonesian version, this 5-item scale was satisfactorily reliable and valid to measure self-efficacy of career decision-making.